2013
DOI: 10.1017/s1461145713000102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic associations of MAOA and NR3C1 with depression and childhood adversities

Abstract: Monoamine oxidase A (MAOA) harbours a polymorphic upstream variable-number tandem repeat (u-VNTR). The MAOA-L allele of the u-VNTR leads to decreased gene expression levels in vitro and has been found to increase the risk of conduct disorder in males with childhood adversities. Early-life adversities have been associated with hypermethylation of the glucocorticoid receptor (NR3C1). In this study, we first performed a genetic association analysis of the MAOA u-VNTR using individuals with depression (n = 392) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
168
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(188 citation statements)
references
References 74 publications
17
168
1
2
Order By: Relevance
“…On the contrary, the present results contradict those of the 2 former studies which found an opposing pattern of an increased incidence of depressive symptoms in MAOA-L carriers with childhood stress [16, 17]. It has to be noted that both studies operationalized life stress as childhood adversities and only asked for maltreatment and abuse in the case of Cicchetti et al [16] and for parental death, parental divorce, financial problems, and other familial constraints in the case of Melas et al [17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the present results contradict those of the 2 former studies which found an opposing pattern of an increased incidence of depressive symptoms in MAOA-L carriers with childhood stress [16, 17]. It has to be noted that both studies operationalized life stress as childhood adversities and only asked for maltreatment and abuse in the case of Cicchetti et al [16] and for parental death, parental divorce, financial problems, and other familial constraints in the case of Melas et al [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have shown an interaction between 5-HTTLPR genotype and life stress on depressive symptoms [13, 14]. While some authors have presented data suggesting a GxE interaction of MAOA-uVNTR and life stress on anti-social behavior [15], there are only very few studies testing an interaction of these 2 factors on depression [16, 17]. Both studies find an increased risk for depression in female carriers of the MAOA-L allele who have experienced childhood adversities.…”
Section: Introductionmentioning
confidence: 99%
“…Gene-environment studies on (MAOA-uVNTR) have demonstrated that a genotype related to low monoamine oxidase activity is associated with antisocial behavior in the presence of childhood maltreatment ). An interaction effect between MAOA and childhood adversities on depression have also been noted (Cicchetti, Rogosch, & Sturge-Apple, 2007;Melas et al, 2013).…”
Section: Maoamentioning
confidence: 89%
“…However, VNTRs may be part of inheritance mechanisms and evolution in a much broader perspective than the inheritance of absolutely necessary abilities. Tandem repeats located within gene-coding regions are frequent in the human genome as well as in other organisms studied, and is associated with neurodegenerative diseases [38] and with the imprint of childhood adversities on the genetic risk factors for adult depression [39]. We therefore speculate that VNTRs may be involved in the inheritance of biological vulnerability, thereby justifying this explorative study of host and bacterial determinants of severe infection by MLVA.…”
Section: Mtc-h (11 Strains)mentioning
confidence: 95%